Electromagnetic band gap (EBG) antenna design - Muhammad Adib Sharhan Bin Shariff (2016)
Microstrip antenna technology has brought a new leading edge to wireless communication system. It is extensively utilised in many commercial and military applications today such as satellite communications, surveillance and missile guidance system. Its advantages are underlined on its geometrical characteristics, electrical performance and simple fabrication. The progressive technological advancement demands for higher antenna performance in which it has been a continual research. The optimization of antenna design is highlighted as a key to enhance performance of antenna.